Alternative parameterization for assessing branch outages by a continuation method - Matarucco, R. R.; Alves, D. A. [UNESP]; Da Silva, L. C.P.; Castro, C. A. (My University, 2004)
This paper proposes and tests new parameters, namely the voltage magnitudes, phase angles and the total power losses, for evaluating the effects of branch outages. The approach can be used as a verification tool after a list of critical contingencies had been ranked according to their severities by the contingency selection function. It is then possible to find whether the non-convergence of a power flow is due to a numerical problem or to an infeasible operating situation. Besides, the proposed parameters have a clear physical meaning rather than geometrical and allow the development and application of continuation methods for power systems contingency analysis. The main advantage of using the total real power losses as a parameter is that it is not necessary to change parameters during the solutions tracing until beyond the simple limit point, where the original Jacobian is singular. Results are presented for the IEEE 14 and 57 bus test system. © 2004 IEEE.
Keywords: Contingency analysis; Continuation Method; Parameterization; Voltage Stability